Safe emergency neonatal airway management: current challenges and potential approaches. Issue 3 (21st April 2021) - O'Shea, Joyce E; Scrivens, Alexandra; Edwards, Gemma; Roehr, Charles Christoph
Abstract : This review examines the airway adjuncts currently used to acutely manage the neonatal airway. It describes the challenges encountered with facemask ventilation and intubation. Evidence is presented on how to optimise intubation safety and success rates with the use of videolaryngoscopy and attention to the intubation environment. The supraglottic airway (laryngeal mask airway) is emerging as a promising neonatal airway adjunct. It can be used effectively with little training to provide a viable alternative to facemask ventilation and intubation in neonatal resuscitation and be used as an alternative conduit for the administration of surfactant. Abstract : This review describes the challenges encountered with neonatal intubation, particularly in relation to training and achieving competency. It discusses strategies to optimise intubation success and examines the airway adjuncts currently available to manage the neonatal airway.